Bidirectional Synergistic Vergence. (3rd September 2015) - Gokce, Gokcen; Ozgonul, Cem; Cagatay, Halil Huseyin; Ekinci, Metin; Ceylan, Osman Melih; Mutlu, Fatih Mehmet
ABSTRACT: A 14-year-old boy presented with left ptosis and squint since his childhood. In primary position he had left hypotropia with ptosis (levator function 2 mm). With elevation of the right eye, the left eye depresses and adducts; with depression of the right eye, the left eye elevates and abducts. Forced duction test revealed no restrictive pattern. The synergistic divergence described in the literature was unidirectional and wholly compatible with inferior rectus co-contraction. But this case is bidirectional, and the aberrant upward movement cannot be explained by rectus muscle co-contraction. The two vertical rectus muscles show reciprocal misinnervation, or this effect could be coming from co-contraction of one of the oblique muscles for the movement in one direction.